Kedudukan Dan Hak Ahli Waris Terhadap Harta Warisan Menurut Kitab Undang – Undang Hukum Perdata - Jessica Manuela Lewerissa; Barzah Latupono; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: If someone dies, then all of his rights and obligations are transferred or transferred to his heirs. Purposes of the Research: This writing aims to find out the position of the heir to the inheritance, to find out who is entitled to the inheritance left by.Methods of the Research: The research method is very important to get accurate data so that it is said to be a tool or a way to guide in conducting research.Results of the Research: In the event of the death of a person, which is a legal event, it also causes legal consequences in the management and continuation of the matters and obligations of a person who dies. In addition, the occurrence of a position and the rights of the heirs will have consequences in the position and rights of the heirs to the inheritance. In addition, when viewed from the four groups above, they inherit sequentially, namely first those who are called or act as heirs of group I, then only groups II, III, and IV. In connection with the case example, all of the heirs have the same position and rights over the inheritance of the heirs, even Out-of-Marriage Children can inherit by replacement of place or better known as in Dutch "plaatsvervulling" and Out-of-Marriage Children inherit part of the rights from their parents. who has died Thus the Civil Code does not recognize the difference between men and women, married or unmarried, adults or underage, all of whom are considered as heirs who have the same position and rights over part of the inheritance which is an inherited property. left by the heir. Thus, if viewed from the examples of the cases studied, it can be seen that all children of the descendants of their heirs are entitled to enjoy the inheritance because the heirs have 7 children, so each division gets 1/7 of the inheritance. In addition, it is also necessary to know that if the testator wants to give his property before he dies to one of his children, it should be given with a written will or made by an authorized official.